"Daj Boże Oświecenie w Polsce!". Określenia Boga w pierwszym roczniku czasopisma "Monitor" = "God, Give the Enlightenment in Poland!". Names of God in the first issue of "Monitor" - Gorzelana, Joanna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The paper depicts the names of God present in the journal "Monitor" in 1765. The maga?zine, while promoting Enlightenment slogans, did not undermine the faith in God. Therefore, the following names of God appear in the periodical: the Creator (Stwórca), the Ruler (Pan Najwyższy, Pan Zastępów), the Guardian (Opatrzność) and the Judge (wyrok boski, boski urząd sądzenia). There are also conventionalized phrases (uchowaj Boże, daj Boże) which reflect the religious belief of the editors or Monitor's readers corresponding with them.
Keywords: oświecenie - literatura; "Monitor" - czasopismo; Bóg; religia; Polish Enlightenment; religion; God